2021
DOI: 10.1073/pnas.2022078118
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom segregation of sister chromosomes by Escherichia coli MukBEF

Abstract: Structural maintenance of chromosomes (SMC) complexes contribute to chromosome organization in all domains of life. In Escherichia coli, MukBEF, the functional SMC homolog, promotes spatiotemporal chromosome organization and faithful chromosome segregation. Here, we address the relative contributions of MukBEF and the replication terminus (ter) binding protein, MatP, to chromosome organization–segregation. We show that MukBEF, but not MatP, is required for the normal localization of the origin of replication t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
(163 reference statements)
1
12
1
Order By: Relevance
“…Alternatively, the CLs may arise due to SMC proteins such as MukBEF which are known to create contacts between segments separated by ∼900 kbp. 32,61 Previous studies already suggest that the E. coli chromosome is organized into ‘loop domains’. 62–64 It has also been shown previously that depletion of some SMC proteins like MukBEF leads to defects in the segregation of the E. coli chromosome, thus underlining their importance.…”
Section: Modelmentioning
confidence: 99%
“…Alternatively, the CLs may arise due to SMC proteins such as MukBEF which are known to create contacts between segments separated by ∼900 kbp. 32,61 Previous studies already suggest that the E. coli chromosome is organized into ‘loop domains’. 62–64 It has also been shown previously that depletion of some SMC proteins like MukBEF leads to defects in the segregation of the E. coli chromosome, thus underlining their importance.…”
Section: Modelmentioning
confidence: 99%
“…ATPase activity is essential for in vivo function, as mutant MukB proteins that are deficient in ATP hydrolysis (MukB E1407Q , hereafter referred to as Muk-B EQ ) or ATP binding (MukB D1406A , hereafter referred to as MukB DA ) display ΔmukB phenotypes 6,17,18 . Cells lacking functional MukBEF, grown in a minimal medium under permissive conditions, have disorganized chromosomes with misplaced genetic loci, and fail to properly segregate sister chromosomes, leading to anucleate cell production 4,6,[18][19][20] . Furthermore, ΔmukB cells are inviable during rapid growth that supports overlapping replication cycles, apparently because of failures in chromosome segregation 4,6,18,20 .…”
mentioning
confidence: 99%
“…MukBEF and MatP are not merely factors that set the density of the chromosome, but they also play a major role in DNA segregation. For instance, MukBEF was recently shown to direct newly replicated origins towards the daughter cells 12 , and as a result, deletion of MukB resulted in anucleated cells and in cells that have unsegregated oriC at the older cell pole. MatP was conversely shown to be necessary for the proper localization of the ter domain after segregation and subsequent cell division 43 and MatP was found to be involved in sister cohesion during the chromosomal movement right before cell division 44 .…”
Section: Discussionmentioning
confidence: 99%
“…DNA can be bound and re-shaped in vitro by the hinge-like configuration of the MukB subunits in an ATP-dependent manner 10 . Recent studies reported that a 6-fold increase in the number of MukBEF copies led to the formation of a ring-like structure of SMCs along the toroidal nucleoid 11,12 . This ring was hypothesized to function as a chromosomal backbone from which peripheral DNA loops protrude.…”
Section: Introductionmentioning
confidence: 99%